Adangiyah: Philosophy of Art in Tradition and Modernization - Bambang Sunarto (Pascasarjana Institut Seni Indonesia Surakarta, 2021)
Dewa Ruci's journal on this edition is felt so special. Since volume 15 has been eager to target a wider audience. Many scientific idiographic concepts are important and need to be known by international readers. This edition is proud to present the most widely written articles by postgraduate students and lecturers from the Indonesian Institute of the Arts Surakarta, Universities of Education from Surabaya, and Malang (East Java). What is special about this edition of this journal is the participation of the second author, who comes from various countries who are very encouraging to the first author. The participating writers from abroad are Adzrool Idzwan Ismail (Malaysia), Michiyo Yoneno Reyes (Japan), Nazima Rangwala Kalita (India), Lee Yong-Shik (South Korea), Jody Diamond (United States).We above appear to have six collaboratively written articles to publish on this occasion. The first author, Soerjo Wido Minato, wrote an article entitled “Art, Nature, and Culinary As Leverages for Village Branding at the Foot of the Mountain.” He discussed that coastal tourism and coastal villages have always been attractions, especially mountain villages that have succeeded in branding themselves as tourist villages. The Malang State University research team conducted research activities to support the preparation of Benjor Village to become a tourist village. An effective strategy for branding Benjor Village as a tourist village at the foot of the mountain is to synergize art, nature, and culinary arts in logos, songs, dances, taglines, videos, and social media.Next is Yulela Nur Imama's article entitled